2018
DOI: 10.6025/ijwa/2018/10/4/127-136
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media Usage and Prevalence of Internet Addiction among Undergraduate Students in South Africa

Abstract: Internet and digital media for educational purposes have significantly improved knowledge creation. The Internet has proven itself to be a valuable resource in the enhancement of knowledge production and dissemination. The purpose of the study was to establish how excessive non-academic use of the Internet detrimentally affects undergraduate students' daily lives. Using survey design, a total of 390 University undergraduate students comprising mainly adolescents/ young adults were selected using stratified ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
3
16
3
Order By: Relevance
“…In this study, university students spending a long time (more than 5 h per day) on the internet increased the likelihood of internet addiction, which is consistent with findings from other studies [ 14 , 16 , 21 , 24 ]. An excessive amount of time spent on the internet serves as a distraction from schoolwork.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, university students spending a long time (more than 5 h per day) on the internet increased the likelihood of internet addiction, which is consistent with findings from other studies [ 14 , 16 , 21 , 24 ]. An excessive amount of time spent on the internet serves as a distraction from schoolwork.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a study in Iraq [ 10 ] utilized an 8-item scale as opposed to the 20-item scale used in this study. In contrast, [ 16 , 21 ] utilized a modified version of the scale, and [ 5 ] used a different tool (i.e., Chen Internet Addiction Scale) to assess internet addiction. Higher prevalence may also be attributed to internet access using personal devices, considering that more than 70% of all respondents in this study accessed the internet using their mobile devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 In another study by Salubi et al of all subject 282 (72.3%) of the respondents indicated that they make use of the internet daily with 34.8% spending more than 10 hours. 19 Patel et al observed that out of total 172 participants, 5.73% of students had internet addiction. More than half of the students with internet addiction were using internet for 5 years or more.…”
Section: Discussionmentioning
confidence: 99%